Doppler Flow Response Following Running Exercise Differs Between Healthy and Tendinopathic Achilles Tendons - Risch, Lucie; Mayer, Frank; Cassel, Michael (Frontiers in Physiology, 2021)
The relationship between exercise-induced intratendinous blood flow (IBF) and tendon pathology or training exposure is unclear. This study investigates the acute effect of running exercise on sonographic detectable IBF in healthy and tendinopathic Achilles tendons (ATs) of runners and recreational participants. 48 participants (43±13 years, 176±9 cm, 75±11 kg) performed a standardized submaximal 30-minute constant load treadmill run with Doppler ultrasound “Advanced dynamic flow” examinations before (Upre) and 5, 30, 60, and 120 min (U5-U120) afterwards. Included were runners (>30 km/week) and recreational participants (<10 km/week) with healthy (Hrun, n=10; Hrec, n=15) or tendinopathic (Trun, n=13; Trec, n=10) ATs. IBF was assessed by counting number [n] of intratendinous vessels. IBF data are presented descriptively (%, median [minimum to maximum range] for baseline-IBF and IBF-difference post-exercise). Statistical differences for group and time point IBF and IBF changes were analyzed with Friedman and Kruskal-Wallis ANOVA (ɑ= 0.05). At baseline, IBF was detected in 40% (3 [1-6]) of Hrun, in 53% (4 [1-5]) of Hrec, in 85% (3 [1-25]) of Trun, and 70% (10 [2-30]) of Trec. At U5 IBF responded to exercise in 30% (3 [-1-9]) of Hrun, in 53% (4 [-2-6]) of Hrec, in 70% (4 [-10-10]) of Trun, and in 80% (5 [1-10]) of Trec. While IBF in 80% of healthy responding ATs returned to baseline at U30, IBF remained elevated until U120 in 60% of tendinopathic ATs. Within groups, IBF changes from Upre-U120 were significant for Hrec (p<0.01), Trun (p=0.05), and Trec (p<0.01). Between groups, IBF changes in consecutive examinations were not significantly different (p>0.05) but IBF-level was significantly higher at all measurement time points in tendinopathic versus healthy ATs (p<0.05). Irrespective of training status and tendon pathology, running leads to an immediate increase of IBF in responding tendons. This increase occurs shortly in healthy and prolonged in tendinopathic ATs. Training exposure does not alter IBF occurrence, but IBF level is elevated in tendon pathology. While an immediate exercise-induced IBF increase is a physiological response, prolonged IBF is considered a pathological finding associated with Achilles tendinopathy.